Testing the Impact of Vibration on Changes in the Number of Erythrocytes and Platelet Counts in Whole Blood - Muhamad Syamsul Arif Setiyo Negoro; Jessica Juan Pramudita; Lutfi Rusyadi (Jurnal Biosains Pascasarjana, 2022)
Blood or plasma is transferred from the unit car to the Blood Donor Unit using a conventional cooler box without any tools to maintain the effect of vibration which is very possible for a decrease in blood quality. Examination carried out to determine the quality of blood through routine hematological examination by counting the number of erythrocytes and platelets. The purpose of this study was to determine the impact of vibration on the number of red blood cells and thrombocytes. The research design was a pre and post test with control group design. The sample size for each group was nine tubes of blood. Data was processed by one way ANOVA and tukeys HSD test. Results There was a significant difference in the number of erythrocytes between the group that was vibrated at a frequency of 11 HZ compared to the group that was vibrated at a frequency of 0 HZ and 5 HZ with p values 0.00 and 0.01, respectively. There was a significant difference in the number of platelets between the groups that were vibrated with a frequency of 11 HZ compared to the groups that were vibrated with a frequency of 0 HZ and 5 HZ with a p value of 0.00. It was concluded that vibrations exceeding 10 Hz could decrease the number of erythrocytes and platelets in whole blood